Femoroacetabular impingement: presence of FAI-like features on conventional radiography in young patients presenting to primary care with hip pain. (July 2013) - Sullivan, Carl; Chakraverty, Julian; Foley, Kieran; Narayanaswamy, Srikanth; Kamath, Sridhar
Background: Femoroacetabular impingement (FAI) is a recognized major cause of early osteoarthritis in the hip and tends to present in young and active patients. The presence of morphological parameters associated with, or predisposing to FAI on radiographs can guide referral to a hip specialist for further assessment. Purpose: To determine the presence of radiographic findings with a known association with FAI in young patients presenting to primary care with hip pain. Material and Methods: Retrospective review of 223 consecutive patients presenting with hip pain (age range, 20–40 years) who underwent a pelvic radiograph in a 6-month period. Patients with pre-existing hip disease and/or technically inadequate radiographs were excluded from the study. Radiographs were analyzed for the presence of radiographic signs associated with FAI: acetabular cross-over sign; prominent posterior wall sign; coxa profunda; protrusio acetabula; acetabular index; lateral center edge angle; pistol grip deformity; and herniation pits. Results: Of the initial 223 patients, 33 (17 women, 16 men; age range, 21–40 years; mean age, 33 years) were included in the study after strict application of exclusion criteria. Sixty-four of 66 joints (33/34 [97%] female joints and 31/32 [97%] male joints) had at least one abnormal finding associated with FAI. Forty-three of 66 joints (23/34 [68%] female joints and 20/32 [63%] male joints) had two or more parameters associated with FAI. All of these abnormal radiographs had initially been reported as normal. Conclusion: Our study demonstrates a high presence of FAI-like radiographic features in a young symptomatic population; these are often not mentioned in the radiology report.